The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fphys.2017.01119
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Emissions in E-cigarette Aerosol: A Systematic Review and Methodological Considerations

Abstract: Carbonyl emissions from tobacco cigarettes represent a substantial health risk contributing to smoking-related morbidity and mortality. As expected, this is an important research topic for tobacco harm reduction products, in an attempt to compare the relative risk of these products compared to tobacco cigarettes. In this study, a systematic review of the literature available on PubMed was performed analyzing the studies evaluating carbonyl emissions from e-cigarettes. A total of 32 studies were identified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 56 publications
4
96
0
1
Order By: Relevance
“…Our results suggest that aerosol yield and liquid consumption per day were the main determinants of the differences in daily formaldehyde and acetaldehyde exposure between conditions. This finding is in agreement with studies reporting that while aldehydes levels per puff are dependent on power settings, aldehydes levels per gram liquid consumption are independent of power settings when the devices are used in realistic conditions 15,18 . Still, a limitation of this particularly analysis is that there may not be enough statistical power to detect differences between conditions in aldehyde exposure per g of liquid consumption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that aerosol yield and liquid consumption per day were the main determinants of the differences in daily formaldehyde and acetaldehyde exposure between conditions. This finding is in agreement with studies reporting that while aldehydes levels per puff are dependent on power settings, aldehydes levels per gram liquid consumption are independent of power settings when the devices are used in realistic conditions 15,18 . Still, a limitation of this particularly analysis is that there may not be enough statistical power to detect differences between conditions in aldehyde exposure per g of liquid consumption.…”
Section: Discussionsupporting
confidence: 92%
“…These studies clearly illustrate that when nicotine is reduced, vapers are likely to engage in compensatory behavior by increasing the power on their devices and/or puffing more intensively. Both power 8,15 and puffing topography 30 may affect toxicant emissions, but the extent to which such compensatory behavior affects daily toxicant exposure and subsequent health risk is unknown.…”
mentioning
confidence: 99%
“…However, these findings have been questioned with replication studies showing either lower carbonyl emissions or unrealistic testing conditions that created overheating and dry puffs . A recent systematic review of carbonyl emissions from e‐cigarettes identified several methodological issues which could result in reporting findings with questionable clinical context .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, E-liquids are comprised of only a few ingredients (i.e., propylene glycol (PG) or vegetable glycerin (VG) ± nicotine and flavorings), of which the myriad of available flavors [40] appear to provide most of the detriment to the ECIG user [41][42][43][44][45] when inhaled. Regardless of the apparent "harm reduction" provided by ECIGs, more research is needed to determine additional health related risks [34], especially since it is known that vaporization of E-liquid can induce chemical alterations yielding substances (such as carbonyl emissions) that could potentially cause lung injury [46,47]. In contrast to generic ECIG-generated aerosol, inhalation of aerosol containing cannabis products, especially those bought on the black market, are known to contain vitamin E acetate, a chemical that has been shown to be extremely dangerous, resulting in serious lung injury and even death [48].…”
Section: Introductionmentioning
confidence: 99%